GROWING Nutritious Foods, GROWING Futures: The first cycle of the gender-transformative integrated climate smart agriculture-nutritionmarketing intervention gets off the ground in Northern Ghana - Temesgen, B.B.; Gyan-Bassaw, P. (International Potato Center, 2023)
With the completion of the Project Implementation Plan in October 2022, work setting up the first two-year cycle of GROWING Future Clubs (GFCs) among households with young children in 36 communities began in earnest, focusing first on ensuring agricultural interventions occurred in a timely manner, then nutrition trainings, and getting gender champions in place to initiate gender dialogues at district and local levels. Much is being learned that will inform and improve the integrated intervention by the start of Cycle 2 in December 2023.